2016
DOI: 10.1002/qj.2951
|View full text |Cite
|
Sign up to set email alerts
|

Properties and temporal variability of summertime temperature inversions over Dronning Maud Land, Antarctica

Abstract: The occurrence, properties and temporal variations of temperature inversions over Dronning Maud Land, Antarctica, were examined on the basis of tethersonde and 10 m tower measurements during the austral summer 2010-2011. Temperature inversions occurred in 96% of the observed tethersonde profiles, and a surface-based inversion in 58% of the profiles. Although the sun did not set during the study period, the amplitude of solar radiation was large enough to generate a diurnal cycle in near-surface temperatures, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Another important factor influencing the relative frequency was the use of radio sounding in other studies, which enables better vertical resolution. Nygård et al (2017) used tethersondes over Aboa (Queen Maud Land) to study summertime TI and mostly detected several thin inversion layers with a vertical extension of less than 100 m. Consequently, it is likely that in our observations from 8 to 375 m a.s.l., we actually detected the base of one inversion layer and the top of another one above the surface-based TI. However, as the primary aim of this study was to reveal interannual variability, the length of the study period had a priority.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Another important factor influencing the relative frequency was the use of radio sounding in other studies, which enables better vertical resolution. Nygård et al (2017) used tethersondes over Aboa (Queen Maud Land) to study summertime TI and mostly detected several thin inversion layers with a vertical extension of less than 100 m. Consequently, it is likely that in our observations from 8 to 375 m a.s.l., we actually detected the base of one inversion layer and the top of another one above the surface-based TI. However, as the primary aim of this study was to reveal interannual variability, the length of the study period had a priority.…”
Section: Discussionmentioning
confidence: 87%
“…Stable boundary layer can be formed over larger areas or can further intensify in anticyclonic conditions due to subsidence (Schwerdtfeger 1970;Baas et al 2019). Nygård et al (2017) showed that both cold-air advection and long-wave radiative cooling can contribute to development and strengthening of surface-based inversion layer in Dronning Maud Land (Antarctica).…”
Section: Introductionmentioning
confidence: 99%
“…The mixing height of the atmospheric boundary layer and wind speed and direction are influenced by a number of factors, including the amount of solar and surface stored energy and terrain inhomogeneity (Carbone et al, 2010). The atmospheric boundary layer can be investigated through various means, including balloon-borne soundings, tethersondes, dropsondes and hot-air balloons (e.g., Laakso et al, 2007;Greenberg et al, 2009;Nygård et al, 2017); towers (e.g., Heintzenberg et al, 2011;Andreae et al, 2015); remote sensors, including ceilometers, sodars, Doppler lidars and radar techniques (e.g., O'Connor et al, 2010;Schween et al, 2014;Vakkari et al, 2015); and conventional research aircrafts (Hermann et al, 2003;Twohy et al, 2002;Benson et al, 2008). Unmanned aerial systems (UASs) have recently gained popularity as measurement platforms in atmospheric research.…”
Section: Introductionmentioning
confidence: 99%
“…In situ observation of PBL Published by Copernicus Publications. D. Brus et al: Aerosol, gases, and meteorological parameters measured during LAPSE-RATE properties are obtained through various techniques, including balloon soundings, tethersondes, dropsondes and hot-air balloons (e.g., Laakso et al, 2007;Greenberg et al, 2009;Nygård et al, 2017), towers (e.g., Heintzenberg et al, 2011;Andreae et al, 2015), and recently by unmanned aerial systems (UASs) (e.g., Ramanathan et al, 2007;Jonassen et al, 2015;Kral et al, 2018;Nolan et al, 2018;Barbieri et al, 2019;Girdwood et al, 2020;Harrison et al, 2021;Jensen et al, 2021;Pinto et al, 2021;Wenta et al, 2021).…”
Section: Introductionmentioning
confidence: 99%